Pengaruh Enterprise Risk Management dan Intellectual Capital Terhadap Kinerja Perusahaan Manufaktur pada Bursa Efek Indonesia Tahun 2020 – 2023 - Sari, Kristina Diana; Marsiwi, Dwiati; Ardiana, Titin Eka (Universitas Muhammadiyah Ponorogo, 2024)
This study examines the influence of Enterprise Risk Management (ERM) and Intellectual Capital (IC) on the performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The research is motivated by the significant challenges faced by manufacturers amid the COVID-19 pandemic, which impacted production, revenue, and overall corporate performance. The study aims to explore how ERM implementation and the management of intellectual capital affect firm performance, considering firm size as a control variable.A quantitative research method with multiple linear regression analysis was applied using secondary data from annual financial reports of manufacturing companies listed on IDX. The sample consisted of 223 observations selected via purposive sampling, after excluding outliers. Data processing utilized SPSS software, accompanied by classical assumption tests such as normality, multicollinearity, and autocorrelation tests to validate the regression model. Findings reveal that ERM positively and significantly impacts firm performance, while IC shows a negative yet significant influence. Firm size also has a positive and significant effect. The regression model accounts for 43.4% of the variance in firm performance, indicating the critical role of risk management, intellectual capital, and firm size in shaping manufacturing firms’ performance during and after the COVID-19 period. Keywords: Enterprise Risk Management, Intellectual Capital, Firm Size, Firm Performance, Manufacturing Companies, Indonesia Stock Exchange